2014
DOI: 10.3748/wjg.v20.i29.9922
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriand oral pathology: Relationship with the gastric infection

Abstract: Helicobacter pylori (H. pylori) has been found in the oral cavity and stomach, and its infection is one of the most frequent worldwide. We reviewed the literature and conducted a Topic Highlight, which identified studies reporting an association between H. pylori-infection in the oral cavity and H. pylori-positive stomach bacterium. This work was designed to determine whether H. pylori is the etiologic agent in periodontal disease, recurrent aphthous stomatitis (RAS), squamous cell carcinoma, burning and halit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 103 publications
1
96
1
13
Order By: Relevance
“…Adler et al in a review hypothesized that oral microflora may be a permanent reservoir of H. pylori, which is still controversial and they stated that recovery of H. pylori in the mouth is probably intermittent, associated with GERD, but not with specific oral diseases. 17 In contrast to our results, Elsheikh and Mahfouz observed association of H. pylori in RAS. 16 However, in the present study, we could not determine the association of H. pylori in patients with RAS and in patients with RAS and concomitant gastric ulcers as the sample size was too small.…”
Section: Resultscontrasting
confidence: 56%
“…Adler et al in a review hypothesized that oral microflora may be a permanent reservoir of H. pylori, which is still controversial and they stated that recovery of H. pylori in the mouth is probably intermittent, associated with GERD, but not with specific oral diseases. 17 In contrast to our results, Elsheikh and Mahfouz observed association of H. pylori in RAS. 16 However, in the present study, we could not determine the association of H. pylori in patients with RAS and in patients with RAS and concomitant gastric ulcers as the sample size was too small.…”
Section: Resultscontrasting
confidence: 56%
“…Several investigators have detected H. pylori in dental plaque and saliva, and also showed that periodontal pockets ! 5 mm in depth are associated with increased odds of H. pylori seropositivity (43)(44)(45)(46). Therefore, long-term H. pylori infection is considered to cause not only gastric mucosal atrophy, but also periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…9 Some studies indicate that the H. pylori strains isolated from the oral cavity differ from gastric strains, whereas other researchers have stated that identical strains are present in both the oral cavity and the stomach. 7,10 In most cases, patients who tested positive for H. pylori in the oral cavity also had positive gastric biopsy results, but a large number of patients with gastric infections do not present co-infection in the oral cavity.…”
mentioning
confidence: 99%